Langerin+ CD8α+ Dendritic Cells Drive Early CD8+ T Cell Activation and IL-12 Production During Systemic Bacterial Infection - Kelly A. Prendergast; Kelly A. Prendergast; Naomi J. Daniels; Troels R. Petersen; Ian F. Hermans; Ian F. Hermans; Ian F. Hermans; Joanna R. Kirman; Joanna R. Kirman (Frontiers in Immunology, 2018)
Bloodstream infections induce considerable morbidity, high mortality, and represent a significant burden of cost in health care; however, our understanding of the immune response to bacteremia is incomplete. Langerin+ CD8α+ dendritic cells (DCs), residing in the marginal zone of the murine spleen, have the capacity to cross-prime CD8+ T cells and produce IL-12, both of which are important components of antimicrobial immunity. Accordingly, we hypothesized that this DC subset may be a key promoter of adaptive immune responses to blood-borne bacterial infections. Utilizing mice that express the diphtheria toxin receptor under control of the langerin promoter, we investigated the impact of depleting langerin+ CD8α+ DCs in a murine model of intravenous infection with Mycobacterium bovis bacille Calmette–Guerin (BCG). In the absence of langerin+ CD8α+ DCs, the immune response to blood-borne BCG infection was diminished: bacterial numbers in the spleen increased, serum IL-12p40 decreased, and delayed CD8+ T cell activation, proliferation, and IFN-γ production was evident. Our data revealed that langerin+ CD8α+ DCs play a pivotal role in initiating CD8+ T cell responses and IL-12 production in response to bacteremia and may influence the early control of systemic bacterial infections.